Simulation study for ground-based Ku-band microwave observations of ozone and hydroxyl in the polar middle atmosphere - D. A. Newnham; M. A. Clilverd; M. Kosch; A. Seppälä; P. T. Verronen (Atmospheric Measurement Techniques, 2019)
The Ku-band microwave frequencies (10.70–14.25 GHz) overlap emissions from ozone ( O 3 ) at 11.072 GHz and hydroxyl radical (OH) at 13.441 GHz. These important chemical species in the polar middle atmosphere respond strongly to high-latitude geomagnetic activity associated with space weather. Atmospheric model calculations predict that energetic electron precipitation (EEP) driven by magnetospheric substorms produces large changes in polar mesospheric O 3 and OH. The EEP typically peaks at geomagnetic latitudes of ∼65 ∘ and evolves rapidly with time longitudinally and over the geomagnetic latitude range 60–80 ∘ . Previous atmospheric modelling studies have shown that during substorms OH abundance can increase by more than an order of magnitude at 64–84 km and mesospheric O 3 losses can exceed 50 %. In this work, an atmospheric simulation and retrieval study has been performed to determine the requirements for passive microwave radiometers capable of measuring diurnal variations in O 3 and OH profiles from high-latitude Northern Hemisphere and Antarctic locations to verify model predictions. We show that, for a 11.072 GHz radiometer making 6 h spectral measurements with 10 kHz frequency resolution and root-mean-square baseline noise of 1 mK, O 3 could be profiled over 8×10-4 <svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="42pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="6795c8d189f4e715bc85b29c13e85307"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="amt-12-1375-2019-ie00001.svg" width="42pt" height="14pt" src="amt-12-1375-2019-ie00001.png"/></svg:svg> –0.22 hPa ( ∼98 –58 km) with 10–17 km ...